1989
DOI: 10.1152/ajpendo.1989.257.1.e74
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylase synthesis in diabetic hepatocytes and cardiomyocytes

Abstract: Whereas total cardiac glycogen phosphorylase activity appears to be unaffected by severe insulin deficiency, a diabetes-induced decreased in hepatic glycogen phosphorylase activity has been demonstrated by our laboratory and others using liver extracts, isolated perfused liver, and cultured hepatocytes. The loss of activity in diabetic liver can be correlated with a drop in protein levels. Using primary cultures of cells from normal and diabetic rats and phosphorylase specific antibodies, we found a correspond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 4 publications
1
6
0
Order By: Relevance
“…The decrease in total hepatic phosphorylase activity in diabetic rats has also been observed by other investigators (9,15,18,34). Rulfs et al (18) have further reported that the decrease in total phosphorylase activity is related to the reduction in phosphorylase protein as a result of the decreased synthesis of this protein. In contrast to these results, Bahnak and Gold (9) have observed that the decrease in total phosphorylase protein is due to a more pronounced increase in the degradation rate of phosphorylase.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…The decrease in total hepatic phosphorylase activity in diabetic rats has also been observed by other investigators (9,15,18,34). Rulfs et al (18) have further reported that the decrease in total phosphorylase activity is related to the reduction in phosphorylase protein as a result of the decreased synthesis of this protein. In contrast to these results, Bahnak and Gold (9) have observed that the decrease in total phosphorylase protein is due to a more pronounced increase in the degradation rate of phosphorylase.…”
Section: Discussionsupporting
confidence: 70%
“…Previous studies in our laboratory (8,10,16) and others (9,18) have demonstrated that the activities of phosphorylase and glycogen synthase are altered in the livers of animal models of type 1 insulin-dependent diabetes mellitus. In streptozotocin-or alloxan-induced diabetic animals, the activities of both the active form and the total (i.e.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In our results experimental diabetes caused a decrease of GPa. It was most obvious that lower enzyme activity was caused by a reduction in the enzyme protein level and was presumably due to a decrease in synthesis [48].…”
Section: Discussionmentioning
confidence: 99%
“…Total homogenate protein (100 pg) or 50 pg samples of the 30,OOOg supernatants were run on 8% SDS-polyacrylamide gels and transferred to Immobilon transfer membranes (Millipore, Bedford, MA) overnight at 30 V in 25 mM Tris, 192 mM glycine, pH 8.3, and 20% methanol or for 90 min at 300 mamps in a semidry blotting apparatus (Owl Scientific, Cambridge, MA) in 48 mM Tris, 39 mM glycine, and 10% methanol. Immunodetection was carried out as previously reported (Rulfs et al, 1989) using sheep anti-rat liver synthase as the primary antibody and donkey anti-sheep IgG conjugated to alkaline phosphatase (Boehringer Mannheim, Indianapolis, IN) as secondary antibody. Blots were developed using alkaline phosphate chromogenic substrate (BCIPNBT; Pierce, Rockford, IL) for visualization.…”
Section: Immunoblottingmentioning
confidence: 99%